Retrospective Analysis of Reasons for Presenting to Emergency Ophthalmic Care in Poland and the USA - Literature Review - Aneta Michalczewska; Kaja Marszałek-Moc; Karolina Palacz; Magdalena Miernik-Skrzypczak; Maria Jasiewicz; Monika Kamińska; Patrycja Karnas-Bognacka; Natalia Dąbrowska (Nicolaus Copernicus University in Toruń, 2024)
Introduction. Emergency Department is a hospital unit, where is provided care in in cases of sudden threat to life and health. One of the reasons why patients come to the Emergency Department is eye damage. Emergency ophthalmological services are a very important form of ophthalmological care because some conditions and diseases require quick intervention to prevent permanent vision damage or eye loss. Patients come to hospital emergency departments for many reasons, such as: eyeball injury, sudden pain or unexpected deterioration of vision. It is worth noting that some patients do not understand the provision of services within health care units and in conditions that do not require urgent care, they seek it in emergency rooms. Aim of study. The following study analyzes the reasons for reporting to emergency ophthalmological services in Poland and the United States. Knowing the most common causes of patients' ailments and the factors that influence them, we can plan strategies for providing specific services within health care units. Materials and methods. The work reviews articles published in the years 2005-2023 in Poland and the United States of America. The results obtained from individual studies were divided in terms of age, gender, traumatic and non-traumatic causes. Additionally, it was checked how often patients had to be hospitalized after staying in Polish emergency departments. Conclusions. Injuries and other eye diseases affect patients regardless of gender and age. Most often, these are adult men.